Benin Financial Sector Review : Stability for a Better Inclusion - World Bank (World Bank, Washington, DC, 2019)
This report focuses on the Beninese financial sector by identifying the scope and penetration of specific activities such as banking, microfinance, retail payments, and agriculture finance and the challenges of effectively regulating and supervising such activities, with recommendations aimed at ensuring their financial soundness and achieving regulatory sustainability. The report is organized as follows: chapter one provides a brief overview of the activities of the banking sector, with an emphasis on the level of its contribution in financing the economy, the financial situation and impact on financial stability. Chapter two provides a current state of the microfinance sector, the challenges, and threats that may limit its growth and contribution to the development of the real economy, with recommendations to go forward. Chapter three consists of a diagnosis of the retail payment ecosystem and identifies several recommendations to help increase financial inclusion in Benin. Chapter four provides an overview of the current government interventions to facilitate access to credit in the agriculture sector, the enduring constraints which limit access to and the attractiveness of the private sector, and suggestions to crowd in further private sector financing.